Structural space of intramolecular peptide disulfides: Analysis of peptide toxins retrieved from venomous peptide databases. (June 2017) - Govindu, Panchada Ch. V.; Chakraborty, Priyanka; Dutta, Angshu; Gowd, Konkallu Hanumae
Graphical abstract: Highlights: General equation was derived to predict distinct cysteine patterns for given even number of cysteine residues in a sequence. Structural space of intramolecular peptide disulfides was deduced using combination of cysteine patterns and disulfide isomers. Database analysis of peptide toxins has revealed void difference between theoretically available and naturally selected disulfide folds of peptide toxins. Characteristic features of peptide toxins is presence of the same intramolecular disulfide fold in functionally divergent toxins and poor accessibility of cystine in native folds of toxins. Abstract: Structural space of intramolecular peptide disulfides is the combination of arrangement of even number of cysteine residues in single polypeptide and the disulfide isomers resulting from differential connectivity between cysteine residues. In the current report, we are documenting theoretical analysis and derivation of general formula [ 2 × 4 { ( n 2 ) − 1 } ] to predict possible distinct cysteine patterns for given 'n' even number of cysteine residues in a sequence. Combined formula of predicting distinct cysteine patterns and different disulfide isomers can be used to deduce the truly available structural space of intramolecular peptide disulfides, which may be used in structural analysis of disulfide rich peptides and proteins. In this report, we have also analyzed cysteine patterns and disulfide connectivities of peptide toxins, which is the largest group of intramolecular peptide disulfide natural products, retrieved from publically available animal toxin databases. Observed 29 distinct cysteine patterns of toxins exhibited 61 unique intramolecular disulfide folds, with limitation of having up to eight cysteine residues in a sequence, compared to theoretically available 170 different cysteine patterns generating 13, 946 distinct intramolecular disulfide folds. Database analysis of peptide toxins has also revealed the features of presence of same intramolecular disulfide motif in functionally divergent peptide toxins and adaptation of the same disulfide fold with similar functions in different venomous species. Calculations of relative accessible surface area of cystine and average value of non-cysteine residues in the representative intramolecular disulfide folds of peptide toxins has revealed the feature of poor accessibility of cystine to external agents and their dependency on number of disulfide bonds in the sequence. Implementation of new generation sequencing methods and novel disulfide mapping techniques will unravel hidden diversity of intramolecular disulfide motifs of toxins and current report points to the selection of disulfide motifs in peptide toxins.